A pilot study for identify the factor influencing productive Malaysian cocoa farmers (PMCF) work performance during Covid-19 pandemic - Sulaiman, Winoryantie; Arif Shah, Jasmin; Mohamed Haris, Nur Bahiah; Md. Sail, Rahim; A.Ghani, Mohd. Zamri; Kasin, Ramle (Human Resource Management Academic Research Society, 2022)
Work performance of cocoa farmers played a significant role in contributing more than 95% of cocoa production in Malaysia. The low production was reported due to the low productivity of cocoa beans produced by the farmers. This article aims to describe the process of implementing pilot study to determine the validity and reliability of the instrument for a study on determine the factor that influencing productive Malaysian cocoa farmers (PMCF) work performance. The instrument was adapted, developed, modified and restructured by the researcher based on past research with the variables namely personality traits, knowledge, practice and logistic and work performance. The instrument content also was validated by the field expert expert panel and also answering trial session. A total number of 105 respondents were selected which were 35 respondents each from, peninsular Malaysia, Sarawak and Sabah. The data from the pilot study was analysed by using SPSS 25.0 to determine the validity and reliability of the instrument items. From the, the instrument can be used for the real data collection after some minor adjustment 32 numbers of items and 65 new additional items. Based on the result of the pilot study, the instrument considered valid and reliable.